Effect of deforestation on soil microbial activity a worm-composite can improve quality? A microcalorimetric analysis at 25 °C - Sigstad, Emma Elizabeth (2002)
All crops grow in the soil environment; thus, soil properties are of great importance to determine plant and crop conditions. An index to assess soil fertility is its microbial activity. In this sense, in the present work we report the microbial activity of three soils selected by age of deforestation as determined by microcalorimetry at 25 °C and its correlation with organic matter content and colony formation units in two growth media. Also the effect of a worm-composite, currently used as soil fertiliser, on the poorest soil is evaluated.